2023
DOI: 10.1021/acsaem.3c01927
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Hydrolysate Derived from Biorefinery as a Carbon Coating Source for Silicon–Carbon Anodes in Lithium-Ion Capacitors

Geon Hae Lim,
Dae-Yeon Song,
Min ju O
et al.

Abstract: With growing concerns regarding climate change and environmental pollution, there is increasing interest in affordable renewable resources to support sustainable development. Biomass is an abundant and inexpensive source of energy. One of the most efficient ways to utilize biomass is through biorefinery, which produces alternative energy sources and other high valueadded products. In this study, a silicon−carbon composite anode for lithium-ion capacitors (LICs) is synthesized using hydrolysates generated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Si has a high charge–discharge plateau and extremely high specific capacity . However, it suffers from severe volume expansion, low electronic and ionic conductivity, leading to inferior cycling and rate performance .…”
Section: Anode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Si has a high charge–discharge plateau and extremely high specific capacity . However, it suffers from severe volume expansion, low electronic and ionic conductivity, leading to inferior cycling and rate performance .…”
Section: Anode Materialsmentioning
confidence: 99%
“…However, it suffers from severe volume expansion, low electronic and ionic conductivity, leading to inferior cycling and rate performance . In order to solve the problem of volume expansion of Si-based materials, the incorporation of Si with other materials proves to be a practical and effective solution. , An et al reported a composite material Si/C composed of soft carbon and Si and adjusted the distribution of Si on the surface of soft carbon by adjusting the Si content. The introduction of a small quantity of carbon–silicon composite materials in soft carbon anodes not only enhances the charge–discharge kinetics but also offers surplus lithium to slow down the consumption rate of active lithium during prolonged cycles following anode prelithiation.…”
Section: Anode Materialsmentioning
confidence: 99%
“…1,2 In this respect, researchers have shown a renewed interest in lithium metal anodes (LMAs), owing to their high theoretical capacity of 3860 mA h g −1 and low redox potential of −3.04 V. 3–6 Furthermore, the significance of investigating LMAs has been emphasized due to their use in next-generation battery technologies such as the lithium–air and lithium–sulfur battery systems. 7–14 Unfortunately, practical applications of LMAs have been hindered by dendritic lithium growth, unstable solid electrolyte interfaces (SEI), and infinite volume fluctuation during the deposition of lithium, which cause low coulombic efficiency (CE), degradation of battery performance, and short circuits that are directly related to safety risks. 15,16 Various approaches have been employed to address these issues, such as the optimization of electrolytes, 4,17 construction of artificial SEIs, 18 modification of separators, 19 and adjustment of lithium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The use of alloying-type materials such as Ag, Au, and Sn as lithium deposition sites can lower the lithium nucleation overpotential because of their highly lithiophilic nature. 10,28–32 Ag nanoparticles can form Li–Ag alloys during lithium deposition and function as lithiophilic seeds, leading to selective lithium nucleation and deposition. In other words, the Ag nanoparticles located inside the 3D scaffold react with lithium ions directly to produce solid-solution alloys during the initial phase of electrodeposition, and the solid-solution alloys facilitate efficient lithium deposition onto the 3D scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Various carbon sources have been utilized for the coating of silicon-based materials, including graphite, [13][14][15][16] graphene, [17][18][19] carbon nanotubes [20][21][22] and organic carbon sources [23][24][25] are widely acknowledged. Carbon coating serves to enhance the conductivity while buffering the volume variation of Si, which can well alleviate the series of problems when charging and discharging.…”
Section: Introductionmentioning
confidence: 99%